العوامل المؤثرة في تغيير مدقق الحسابات الخارجي من وجهة نظر مدققي الحسابات / دراسة ميدانيّة في البيئة السورية / - الأمين ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
For any area, the independence in work is necessary to do it properly and so as for auditor the independence is important to enable auditor to work neutrally. This study aims at identifying the reasons behind changing external auditor in Syrian public corporations based on auditors’ perspective themselves to ensure that the change is legal and not based on personal judgements. This study also examines whether there is any pressure or interference on auditor’s work. For the purpose of this study, a questionnaire is designed to collect and distribute data to a sample composed of external auditors. Various statistical analyses are preformed to test the hypotheses set. The factors that maight impact the change of external auditor are classified according to their importance. The results are as follows; § Reasons that are related to the company in which the auditor works have an impact on changing external auditor. § Reasons that are related to auditing offices have an impact on changing external auditor. § Reasons that are related to the application of auditing standards have an impact on changing external auditor. § Changing the auditor has no impact on company’s operations. We further recommend to study the reasons of changing external auditor by using other parties perspective such as stockholders, managers and auditing offices. Besides, we recommend to resume developing accounting and auditing profession to protect external auditor. Finally, an expansion in CPA Committee role in organizing and controlling auditors and auditing offices is required. يعتبر الاستقلال بالنسبة لمدققي الحسابات أمراً ضرورياً للقيام بعملهم بحيادية تامة. تهدف هذه الدراسة إلى التعرف على أسباب تغيير مدقق الحسابات الخارجي في الشركات المساهمة العامة السورية من وجهة نظر مدققي الحسابات الخارجيين أنفسهم، وللتأكد من أن التغيير يتم بشكل قانوني وليس حسب الأهواء الشخصية، وأن المدقق يقوم بعمله دون وجود أية ضغوط أو تدخلات. وتحقيقاً لأهداف الدراسة تمّ تصميم استبانة لهذا الغرض كأداة لجمع البيانات، وتوزيعها على عينة الدراسة التي تتكون من المدققين الخارجيين. وقد أخضعت إجابات المستجوبين للتحليلات الإحصائية المناسبة لاختبار مدى صحة الفرضيات. وتم تبويب هذه العوامل وفقاً لأهميتها النسبية. وتوصلت الدراسة إلى النتائج الآتية: - أن الأسباب المرتبطة بالشركة محل التدقيق(العميل) تؤدي إلى تغيير المدقق الخارجي. - أن الأسباب المرتبطة بتطبيق معايير التدقيق تؤدي إلى تغيير المدقق الخارجي. - أن الأسباب المرتبطة بمكاتب التدقيق تؤدي إلى تغيير المدقق الخارجي. - أن تغيير المدقق الخارجي لا يؤثر على نتائج أعمال الشركة(الأرباح). وقد اختتمت الدراسة بالتوصيات الآتية: - ضرورة القيام بإجراء دراسات أخرى حول أسباب تغيير المدقق الخارجي من وجهة نظر أطراف أخرى، كالهيئة العامة للمساهمين، وإدارات الشركات، ومكاتب التدقيق... - العمل على الاستمرار في تطوير القوانين والتعليمات المتعلقة بمهنة المحاسبة والتدقيق، وذلك لتوفير الحماية اللازمة للمدقق الخارجي. - زيادة وتفعيل دور جمعية المحاسبين القانونيين في الرقابة على المدققين ومكاتب التدقيق.